Satellite Communications in the 5G Era - Sharma, Shree Krishna; Chatzinotas, Symeon; Arapoglou, Pantelis-Daniel (Telecommunications, 2018)
Satellite communications (SatCom) plays a vital role in ensuring seamless access to telecommunications services anytime, and is a viable option for delivering telecommunication services in a wide range of sectors such as aeronautical, military, maritime, rescue and disaster relief. It should be an important component of 5G-and-beyond wireless architectures as it can complement terrestrial telecommunication solutions in various scenarios to provide highly reliable and secure connectivity over a wide geographical area. This book explores promising scenarios for 5G SatCom, novel paradigms for hybrid/integrated satellite-terrestrial integration, and emerging technologies for the next generation of SatCom systems. Topics covered include: Role of SatCom in the 5G Era; 5G satellite use cases and scenarios; SDN-enabled networks, NFV-based scenarios and on-board processing for satellite-terrestrial integration; EHF broadband aeronautical SatCom systems; Next-generation NGSO SatCom systems; Diversity combining and handover techniques for MEO satellites; Non-linear countermeasures for multicarrier satellites; SDN demonstrator for multi-beam satellite precoding; Beam-hopping SatCom systems; Optical on-off keying data links for LEO downlink applications; Ultra-high speed data relay systems; On-board interference detection and localization; Advanced random access schemes for SatCom systems; Interference avoidance, mitigation and dynamic spectrum sharing for hybrid satellite-terrestrial systems; and Two-way satellite relaying.